Immunoglobulin M and G in Virologically Confirmed Dengue Hemorrhagic Fever - Tatang K. Samsi; H. Wulur; D. Sugianto; C. R. Bartz; R. Tan; A. Sie (Paediatrica Indonesiana, 1992)
Starting from September 1987, a one year prospective study on lgM and lgG in dengue hemorrhagic fever, was carried out at the Department of Pediatrics, Sumber War as Hospital West Jakarta. This report describes the preliminary finding of the study from September 1987 through June 1988. Virus isolation and serologic analysis (HI, lgG and lgM capture ELISA) for DHF were done by NAMRU 2 in Jakarta. The subjects were 151 virologically confirmed DHF patients consisting of 82 boys and 69 girls of 6 months - 15 years old. Serum samples were collected: (I) on the day of admission; (II) on the day of discharge and (Ill) 2 weeks after the first samples. Serum samples I, II, and Ill were collected from respectively 151, 131 and 64 subjects on respectively 3.5 ± 1.7; 8.8 ± 2.7 and 16.8 ± 2.1 days of illness. Positive lgM titer from acute sera was observed in 20% of subjects. A positive correlation between HI -lgM and HI -lgG was also observed. The percentage of positive lgM titers rose with the increase of HI titer, the percentage of positive lgG titer was lower than that of /gM but a sudden increase exceeding that of lgM was observed at the HI liter of 320 and more. This study revealed that HI titer of640 and 1280 were indicators for the primary and secondary dengue infection respectively and lgM capture ELISA can be used as a reliable predictor for DHF even more in fatal cases where only single serum is available.